Frequency of Ultrasound Findings in Patients with Mastalgia and Its Association with Age in Gujranwala District - Chaudhary, Sehar; Ali, Abid; Zulfiqar, Taiba (Medical Science Journal for Advance Research, 2023)
Background: Ultrasound is the best-known modality used for screening and diagnosis of breast pathologies. This study determine the ultrasound findings in patients with Mastalgia and its association with age.Aims and Objective:To determine the ultrasound findings in patients with Mastalgia and its association with age in Gujranwala, Pakistan. Material and methods: A retrospective cross sectional study was conducted at Medcare International Hospital Gujranwala, Pakistan. A total of 121 female patients with the history of breast pain were enrolled in present study. The duration of this research work was from July 2021 to December 2021. All patients visiting us with the history of breast pain more than one month were included in the study. Pregnant women, those with hormonal therapy and previously diagnosed and treated cases of breast cancer were excluded. All patients were advised breast ultrasound after history and physical examination. Predesigned questionnaire form was used to collect the data. SPSS was used to analyze the data. Frequency of different findings and their associations were found out using the chi square test. These were then graphically portrayed in the form of tables and graphs. P value < 0.05 was considered as significant.Result: The mean age of the patients was 30.03±8.02 years with age range 10-53 years. Among 121 females who presented with breast pain, maximum frequency 50 (41.3%) was seen in age range of 21-30 years. Fibrocystic changes were seen in 22 (18.2%) patients, parenchymal changes in 20 (16.5%), mass Duct ectasia in 13 (10.7%), lymphadenopathy in10 (8.3%), Solid lesion in 8 (6.6%) and fibro adenoma was seen in 4 (3.3%) females respectively. we had four parameters i.e fibro cystic changes, solid lesion, adenosis and parenchymal changes who were linked significant with age with p-value 0.02, 0.001, 0.012 and 0.009 respectively. Most patients were classified as either BI-RADS 1 (53.7 %) or BI-RADS 2 (27.3%). Conclusion: Patient presenting with mastalgia may have different pathologies. Ultrasound can help to determine the exact cause of mastalgia specially breast diseases in young females for whom mammography is contraindicated.